Personalized Medicine in ANCA-Associated Vasculitis ANCA Specificity as the Guide? - Wallace, Zachary S.; Stone, John H. (Frontiers in Immunology, 2019)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a small- to medium-vessel necrotizing vasculitis responsible for excess morbidity and mortality (1). The AAVs, which include granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), and eosinophilic granulomatosis with polyangiitis (EGPA), are among the most difficult types of vasculitis to treat. Although clinicopathologic disease definitions have been used traditionally to categorize patients into one of these three diagnoses, more recently ANCA specificity for either proteinase 3 (PR3) or myeloperoxidase (MPO) has been advocated for the purpose of disease classification (2). This is because differences in genetics, pathogenesis, risk factors, treatment responses, and outcomes align more closely with PR3- or MPO-ANCA type than with the clinocopathologic diagnosis. Moreover, classifying patients as GPA or MPA can be challenging because biopsies are not obtained routinely in most cases and existing classification systems can provide discrepant classification for the same patient (3). In this review, we address the recent literature supporting the use of ANCA specificity to study and personalize the care of AAV patients (Table 1). We focus particularly on patients with GPA or MPA.